Conservation Scientific Test Procedures In Selected Masonry Heritage Buildings In Malaysia - Tan, Chin Ling (2022)
Since the Portuguese era in Malacca back in the 16th century, many authentic colonial heritage buildings were built in Peninsular Malaysia and Sarawak. Majority of these heritage buildings are masonry structural buildings. After Melaka and George Town were recognised by UNESCO World Heritage Convention as World Heritage Sites on 7th July 2008, heritage building conservation in Malaysia received attention from various parties. Since the establishment of the Department of National Heritage under the National Heritage Act 2005 (Act 645) on 1st March 2006 with the responsibility to preserve, conserve, protect and promote the rich treasures of Malaysian heritage, implementation of scientific tests in heritage building conservation in Malaysia is encouraged and recommended by the Department of National Heritage.